Mycobacterium tuberculosis Dissemination Plays a Critical Role in Pathogenesis - Moule, Madeleine G.; Cirillo, Jeffrey D. (Frontiers in Cellular and Infection Microbiology, 2020)
Mycobacterium tuberculosis is primarily a respiratory pathogen. However, 15% of infections worldwide occur at extrapulmonary sites causing additional complications for diagnosis and treatment of the disease. In addition, dissemination of M. tuberculosis out of the lungs is thought to be more than just a rare event leading to extrapulmonary tuberculosis, but rather a prerequisite step that occurs during all infections, producing secondary lesions that can become latent or productive. In this review we will cover the clinical range of extrapulmonary infections and the process of dissemination including evidence from both historical medical literature and animal experiments for dissemination and subsequent reseeding of the lungs through the lymphatic and circulatory systems. While the mechanisms of M. tuberculosis dissemination are not fully understood, we will discuss the various models that have been proposed to address how this process may occur and summarize the bacterial virulence factors that facilitate M. tuberculosis dissemination.